Association between Serum Ferritin Concentration and Perihaematoma Oedema Volume in Patients with Supratentorial Spontaneous Intracerebral Haemorrhage (Bangladesh Journal of Neurosurgery, 2019)
Background: Stroke (ischaemic & haemorrhagic) is a major cause of mortality and morbidity in the developed as well as in the developing countries. Perihaematoma oedema and haematoma expansion are two important points to be considered when deciding outcome of patients with ICH. Brain damage due to haematoma may be irreversible but the injury from perihaematoma oedema may be reversible. It has been seen that S. ferritin is the most reliable indicator of body iron. Treatment with iron chelators may give better outcome after ICH.Objective: This study was under taken to assess the association between serum ferritin and relative perihaematoma oedema volume.Methodology: This study was a cross sectional observational study that was conducted in the Departments of Neurosurgery & Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU) and Dhaka Medical College Hospital (DMCH) from 1st March, 2014 till 30th September, 2015 on 32 patients (32) who fulfilled the selection criteria were enrolled in this study.Results: In this study, male female ratio was 1:1 and the mean age was 56±15 years. Most of the ICH patients fell in the age group between 41-60 years (53%). During admission, grade-1 (GCS 3- 8) level of consciousness was reported among 45% of patients. All the patients in this study presented with motor deficit that include hemiplegia 20 (62.5%) and hemiparesis 12 (37.5%). Mean value of serum ferritin was found elevated on day 4 (344±406 μg/L) in comparison to day 1 (213.4±123.5μg/ L). Mean value of relative perihaematoma oedema was elevated on day 4 (4±2.7) than day 1 (1.9±1) but it was not statistically significant.Conclusion: In this study after statistical analysis by Pearson’s correlation test we found that there was no significant association between serum ferritin concentration and relative perihaematoma oedema on day-1 and day-4.Bang. J Neurosurgery 2019; 8(2): 77-86